Aperiodic Report Trainers of Teacher Trainers (TTT) Evaluation. No. 4, An Evaluation of Clustering in TTT. - Illinois Univ., Urbana. Center for Instructional Research and Curriculum Evaluation; Illinois Univ., Urbana. Center for Instructional Research and Curriculum Evaluation ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
Information is provided about various aspects of the clustering activities of the TTT program for 1969-70. Specific information about the purposes, means, and outcomes of clustering is presented, as is information about the organization of clusters and the extent of parity in TTT. The data was obtained from observations of meetings by evaluation staff, completed questionnaires of cluster meeting participants, completed interviews of project directors, and communications of the evaluation staff with persons involved in the national TTT program. The data indicated that participants generally agreed with the purpose of the cluster activity. The specific purposes of stimulating exchange and interaction and disseminating information among program components were rated highest in personal importance. The geographic basis of clustering was regarded by many as unsatisfactory, and the usefulness of cluster meetings as a clustering activity was inconclusive. Questionnaire respondents felt that parity seemed to be more extensive at the project than the cluster level, and that at the project level more occurred in planning than in operational aspects. The amount of parity at the project level was viewed with confidence as likely to increase significantly in the future. (MBM)
ERIC Note: Submitted to Consortium of Professional Associations for Study of Special Teacher Improvement Programs.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Classification; Educational Programs; Program Evaluation; Teacher Education; Teacher Education Programs; Teacher Educator Education